Contesting the global order the radical political economy of Perry Anderson and Immanuel Wallerstein - Williams, Gregory P. (SUNY series in new political science., 2020)
Examines how events in the Cold War and post-Cold War periods shaped the intellectual projects of Perry Anderson and Immanuel Wallerstein. Contesting the Global Order explores what it means to be a radical intellectual as political hopes fade. Gregory P. Williams chronicles the evolution of intellectual visionaries Perry Anderson and Immanuel Wallerstein, who despite altered circumstances for radical change, continued to advance creative interpretations of the social world. Wallerstein and Anderson, whose hopes were invested in a more egalitarian future, believed their writings would contribute to socialism, which they anticipated would be a postcapitalist future of relative social, economic, and political equality. However, by the 1980s dreams of socialism had faded and they had to face the reality that socialism was neither close nor inevitable. Their sensitivity to current events, Williams argues, takes on new significance in this century, when many scholars are grappling with the issue of change in a world of declining state power.Gregory P. Williams is Assistant Professor of Political Science and International Affairs at the University of Northern Colorado